Impacts of the photoactive layer's properties on the performance of organic solar cells and photodiodes based on a novel model - Inche Ibrahim, Mohd Lukman (2020)
The objectives of this FRGS project were to develop a novel model that can accurately describe the current-voltage characteristics of organic solar cells and photodiodes and to understand the effect of various device properties on the device performance, particularly the active layer’s properties. A novel model that describes the working principle of organic bulk heterojunction solar cells (or photovoltaic cells) was successfully developed and validated. Then, by using the developed model, the effect of the charge carrier mobility, injection barrier, active layer thickness, and light absorption profile were investigated. It was found that the optimum carrier mobility is about 1 x 10^(-6) m^2V^(-1)s^(-1). Concerning the injection barrier, it should not be larger than 0.1 eV in order to maximize the open-circuit voltage, and thus to maximize the achievable power conversion efficiency (PCE). Furthermore, for a low-recombination-loss organic photovoltaics (OPV) with ideal light trapping, the active layer thickness weakly influences the PCE, whereas for a high-recombination-loss OPV with ideal light trapping, the active layer thickness strongly influences the PCE. It was also found that the use of the correct light absorption profile can be important to accurately predict the current-voltage and the performance of OPVs. Finally, if an OPV has a very high carrier mobility imbalance, the light absorption should be concentrated near the electrode collecting the slower carrier type in order to maximize the PCE of the OPV. However, if an OPV has a mobility imbalance that is not very high, light absorption should be concentrated at the centre of the active layer in order to maximize the PCE of the OPV.